Experimental Evolution Identifies Vaccinia Virus Mutations in A24R and A35R That Antagonize the Protein Kinase R Pathway and Accompany Collapse of an Extragenic Gene Amplification - Brennan, Greg (J Virol, 2015)
Most new human infectious diseases emerge from cross-species pathogen transmissions; however, it is not clear how viruses adapt to productively infect new hosts. Host restriction factors represent one species-specific barrier that viruses may initially have little ability to inhibit in new hosts. For example, viral antagonists of protein kinase R (PKR) vary in their ability to block PKR-mediated inhibition of viral replication, in part due to PKR allelic variation between species. We previously reported that amplification of a weak PKR antagonist encoded by rhesus cytomegalovirus, rhtrs1, improved replication of a recombinant poxvirus (VVΔEΔK+RhTRS1) in several resistant primate cells. To test whether amplification increases the opportunity for mutations that improve virus replication with only a single copy of rhtrs1 to evolve, we passaged rhtrs1-amplified viruses in semipermissive primate cells. After passage, we isolated two viruses that contained only a single copy of rhtrs1 yet replicated as well as the amplified virus. Surprisingly, rhtrs1 was not mutated in these viruses; instead, we identified mutations in two vaccinia virus (VACV) genes, A24R and A35R, either of which was sufficient to improve VVΔEΔK+RhTRS1 replication. Neither of these genes has previously been implicated in PKR antagonism. Furthermore, the mutation in A24R, but not A35R, increased resistance to the antipoxviral drug isatin-β-thiosemicarbazone, suggesting that these mutations employ different mechanisms to evade PKR. This study supports our hypothesis that gene amplification may provide a “molecular foothold,” broadly improving replication to facilitate rapid adaptation, while subsequent mutations maintain this efficient replication in the new host without requiring gene amplification. IMPORTANCE Understanding how viruses adapt to a new host may help identify viruses poised to cross species barriers before an outbreak occurs. Amplification of rhtrs1, a weak viral antagonist of the host antiviral protein PKR, enabled a recombinant vaccinia virus to replicate in resistant cells from humans and other primates. After serial passage of rhtrs1-amplified viruses, there arose in two vaccinia virus genes mutations that improved viral replication without requiring rhtrs1 amplification. Neither of these genes has previously been associated with inhibition of the PKR pathway. These data suggest that gene amplification can improve viral replication in a resistant host species and facilitate the emergence of novel adaptations that maintain the foothold needed for continued replication and spread in the new host.